Pursuit of Honor - Flynn, Vince (New York Simon & Schuster Audio, 2009)
In a new thriller featuring CIA superagent Mitch Rapp, fearless Americans must risk their lives for their country's security, fighting a covert war that can never be discussed, even with their own political leaders.
Unabridged.
Compact discs.
Keywords: Rapp, Mitch (Fictitious character) -- Fiction; Intelligence officers -- Fiction; Terrorism -- Fiction; Audiobooks; Political fiction; Suspense fiction